Correlation Between Imaging Morphological Findings and Laboratory Biomarkers in Patients with Retinal Vein Occlusion - Kazantzis,D.; Sergentanis, T.N.; Machairoudia,G.; Dimitriou, E.; Kroupis, C.; Theodossiadis, G; Theodossiadis, P; Chatziralli, I (Ophthalmol.Ther., 2023)
INTRODUCTION: The aim of this study was to investigate the possible correlation between peripheral blood biomarkers and morphological characteristics of retinal imaging in patients with retinal vein occlusion (RVO). METHODS: Participants in this cross-sectional observational study were 65 consecutive patients (65 eyes) with treatment-naive RVO, who underwent spectral-domain optical coherence tomography (SD-OCT) and fundus fluorescein angiography (FFA). In addition, peripheral blood samples were taken to evaluate full blood count and biochemical parameters. The association between imaging characteristics and laboratory parameters was examined. RESULTS: Eyes with subretinal fluid presented significantly higher neutrophil-to-lymphocyte ratios (p = 0.028). Hyperreflective foci on SD-OCT were found to be associated with higher triglyceride levels (p = 0.024). The presence of cysts on SD-OCT was associated with significantly higher triglycerides (p = 0.010). Central subfield thickness (CST) higher than 464 mum was associated with higher lymphocyte count (p = 0.016) and higher urea (p = 0.015). No significant associations were found between laboratory parameters and intraretinal fluid, ellipsoid zone and external limiting membrane condition, or epiretinal membrane and macular ischemia. CONCLUSIONS: Specific imaging morphological characteristics were found to be associated with laboratory parameters in patients with RVO. These findings may help reveal the pathophysiology of RVO and its correlation with the development of specific clinical signs, while they could guide individualized treatment